Hubungan Antara Efikasi Diri dan Kecemasan Akademik di Kalangan Siswa Kelas 9 di SMP Negeri 35 Medan - Grace Angela Sitanggang; Abdul Munir (CV. Eracita Grup, 2026)
This research aims to examine the relationship between self-efficacy and academic anxiety among ninth-grade students at SMP Negeri 35 Medan. Employing a quantitative correlational design, the study involved 95 students selected through total sampling technique. Data were collected using an adapted self-efficacy scale based on Bandura's theory and an academic anxiety scale referring to Holmes's conceptual framework. Pearson’s Product Moment Correlation analysis revealed a significant negative correlation between self-efficacy and academic anxiety (p < 0.001; r = -0,910). These findings indicate that students with high self-belief are more capable of evaluating academic demands as achievable challenges rather than threats, thereby significantly reducing anxiety responses. Consequently, school counselors must prioritize cognitive restructuring interventions aimed at enhancing students' self-efficacy, rather than solely focusing on technical study skills, to foster psychological resilience during educational transitions.